2018
DOI: 10.1245/s10434-018-6460-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immunohistochemistry and Direct Sequencing Methods for Identification of the BRAFV600E Mutation in Papillary Thyroid Carcinoma

Abstract: IHC using the VE1 antibody is a reliable and highly sensitive method for detecting the BRAF mutation in classic PTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 31 publications
4
27
1
2
Order By: Relevance
“…A higher mutation rate was detected by ddPCR. These results were consistent with previous studies that showed a BRAF V600E mutation rate of 29%‐90% . In the present study, the BRAF V600E mutation was only detected in PTC patients and not in patients with benign nodular thyroid disease, which was also consistent with previous studies …”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…A higher mutation rate was detected by ddPCR. These results were consistent with previous studies that showed a BRAF V600E mutation rate of 29%‐90% . In the present study, the BRAF V600E mutation was only detected in PTC patients and not in patients with benign nodular thyroid disease, which was also consistent with previous studies …”
Section: Discussionsupporting
confidence: 94%
“…Thyroid cancer (TC) is the most common type of endocrine malignancy, and papillary thyroid carcinoma (PTC) accounts for the vast majority (90%) of thyroid malignancies . BRAF V600E has a T1799A point mutation in exon 15, resulting in the substitution of valine for glutamic acid at amino acid 600 (V600E), and it is the most common driver mutation of PTC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anti-BRAF V600E (clone VE1) antibody, a mouse monoclonal primary antibody, is used in the identi cation of the BRAF V600E mutant protein. Previous studies have veri ed the sensitivity and speci city of anti-BRAF V600E (clone VE1) antibody in melanoma [7] and papillary thyroid carcinoma [8] . However, few studies have assessed the reliability of anti-BRAF-V600E immunohistochemistry (IHC) in brain tumors.…”
Section: Introductionmentioning
confidence: 99%